2014
DOI: 10.1177/0363546514547171
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Platelet-Rich Plasma and BMP13 on Rotator Cuff Tendon Injury Healing in a Rat Model

Abstract: While PRP is used in the clinical setting, BMP13 may be explored as a superior biofactor to improve rotator cuff tendon healing and reduce the incidence of retears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 61 publications
3
36
0
Order By: Relevance
“…More importantly, the maximum load and stiffness were increased significantly in the H-dose group from 8 to 16 weeks compared with the other groups in our study. A similar finding was described by Lamplot et al 24 , who investigated the upregulated fibronectin expression of bone morphogenetic protein 13 (BMP13, a growth factor of TGF). Results showed that BMP13 promoted tendon healing, because of its superior biological factor, and reduced the incidence of re-tearing.…”
Section: ■ Discussionsupporting
confidence: 78%
“…More importantly, the maximum load and stiffness were increased significantly in the H-dose group from 8 to 16 weeks compared with the other groups in our study. A similar finding was described by Lamplot et al 24 , who investigated the upregulated fibronectin expression of bone morphogenetic protein 13 (BMP13, a growth factor of TGF). Results showed that BMP13 promoted tendon healing, because of its superior biological factor, and reduced the incidence of re-tearing.…”
Section: ■ Discussionsupporting
confidence: 78%
“…5 The transduction of mice tenocytes with adeno-virus expressing BMP-13 increased the expression of genes involved in tendon healing, stress to failure and stiffness. 21 Our study adds to this body of work, by demonstrating for the first time the regenerative potential of BMP-13 in human IVD cells by inducing matrix production.…”
Section: Bmp-13 In Human Intervertebral Discmentioning
confidence: 72%
“…Due to its role in angiogenesis, it was proposed that it plays a critical role in tendon healing [130]. Recently, an in vivo model of rotator cuff healing showed that VEGF improved biomechanical properties of repaired tissue [131]. However, in two clinical studies, VEGF expression was associated with motion pain and synovial proliferation in patients with impingement syndrome, while a correlation with diabetes was also reported [132, 133].…”
Section: Growth Factorsmentioning
confidence: 99%